Ammonium–crown ether supramolecular cation-templated assembly of an unprecedented heterobicluster–metal coordination polymer with enhanced NLO properties. Issue 19 (11th February 2016) - Zhang, Jinfang; Jia, Ding; Humphrey, Mark G.; Meng, Suci; Zaworotko, Michael J.; Cifuentes, Marie P.; Zhang, Chi
Abstract : An unprecedented heterobicluster-metal coordination polymer has been synthesized by a supramolecular template approach and shown to exhibit enhanced NLO properties. Abstract : An ammonium–crown ether host–guest supramolecular cation-templated synthetic methodology has been developed to construct a structurally unprecedented heterobicluster–metal coordination polymer (HCM-CP1 ) based on tetranuclear clusters [WS4 Cu3 ] + with different connection environments, pentanuclear clusters [WS4 Cu4 ] 2+, and Cu + building metal ions. HCM-CP 1 exhibits enhanced NLO properties, which may be ascribed to the incorporation of diverse building cluster components.